Meningkatkan Kinerja Karyawan PAM Tirta Karajae: Peran Motivasi dan Lingkungan Kerja yang Mendukung - Pauru, Catrin; D'Ornay, Anastasia; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The purpose of this study was to find out that work motivation and work environment have a partial effect on employee performance at the Tirta Karajae Regional Drinking Water Company (PAM), Parepare City. To find out that work motivation and work environment have a simultaneous effect on employee performance at the Tirta Karajae Regional Drinking Water Company (PAM), Parepare City. This research was conducted using a Quantitative Descriptive Method. The data analysis technique used was Multiple Linear Regression Analysis and used the SPSS for windows 20 program. The data used in this study used primary sources from the results of questionnaires that had been filled out by the respondents. The findings from this study indicate that work motivation and work environment have a partial effect on employee performance at the Tirta Karajae Regional Drinking Water Company (PAM), Parepare City. Work Motivation and Work Environment have a simultaneous effect on Employee Performance at the Tirta Karajae Regional Drinking Water Company (PAM), Parepare City.